2020
DOI: 10.1186/s12935-020-01584-2
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of candidate genes expected to be essential for melanoma surviving

Abstract: Introduction Cancers may be treated by selective targeting of the genes vital for their survival. A number of attempts have led to discovery of several genes essential for surviving of tumor cells of different types. In this work, we tried to analyze genes that were previously predicted to be essential for melanoma surviving. Here we present the results of transient siRNA-mediated knockdown of the four of such genes, namely, UNC45A, STK11IP, RHPN2 and ZNFX1, in melanoma cell line A375, then assayed the cells f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 43 publications
1
0
0
Order By: Relevance
“…Depletion of this chaperone was shown to inhibit motility of breast and ovarian cancer cells, 27 , 29 but promoted migration of osteosarcoma and melanoma cells. 30 , 62 This resembles the reported opposite effects of NM-II inhibition on cell migration under different experimental conditions 50 , 63 and may reflect complex regulatory effects of UNC-45A-driven myofilament assembly in motile cells. We observed that loss of UNC-45A inhibited both collective migration of IEC sheets and individual cell passage through membrane pores ( Figure 5A - H ).…”
Section: Discussionsupporting
confidence: 72%
“…Depletion of this chaperone was shown to inhibit motility of breast and ovarian cancer cells, 27 , 29 but promoted migration of osteosarcoma and melanoma cells. 30 , 62 This resembles the reported opposite effects of NM-II inhibition on cell migration under different experimental conditions 50 , 63 and may reflect complex regulatory effects of UNC-45A-driven myofilament assembly in motile cells. We observed that loss of UNC-45A inhibited both collective migration of IEC sheets and individual cell passage through membrane pores ( Figure 5A - H ).…”
Section: Discussionsupporting
confidence: 72%